Year‐Round and Long‐Term Phytoplankton Dynamics in Lake Bonney, a Permanently Ice‐Covered Antarctic Lake. Issue 4 (21st April 2021) - Patriarche, J. D.; Priscu, J. C.; Takacs‐Vesbach, C.; Winslow, L.; Myers, K. F.; Buelow, H.; Morgan‐Kiss, R. M.; Doran, P. T.
Abstract: Lake Bonney (McMurdo Dry Valleys, east Antarctica) represents a year‐round refugium for life adapted to permanent extreme conditions. Despite intensive research since the 1960s, due to the logistical constraints posed by 4‐months of 24‐h darkness, knowledge of how the resident photosynthetic microorganisms respond to the polar winter is limited. In addition, the lake level has risen by more than 3 m since 2004: impacts of rapid lake level rise on phytoplankton community structure is also poorly understood. From 2004 to 2015 an in situ submersible spectrofluorometer (bbe FluoroProbe) was deployed in Lake Bonney during the austral summer to quantify the vertical structure of four functional algal groups (green algae, mixed algae, and cryptophytes, cyanobacteria). During the 2013–2014 field season the Fluoroprobe was mounted on autonomous cable‐crawling profilers deployed in both the east and west lobes of Lake Bonney, obtaining the first daily phytoplankton profiles through the polar night. Our findings showed that phytoplankton communities were differentially impacted by physical and chemical factors over long‐term versus seasonal time scales. Following a summer of rapid lake level rise (2010–2011), an increase in depth integrated chlorophyll a (chl‐a) occurred in Lake Bonney caused by stimulation of photoautotrophic green algae. Conversely, peaks in chl‐a during the polar night were associated with an increase in mixotrophic haptophytes and cryptophytes. Collectively our data reveal that phytoplankton groups possessing variable trophic abilities are differentially competitive during seasonal and long‐term time scales owing to periods of higher nutrients (photoautotrophs) versus light/energy limitation (mixotrophs). Key Points: A profiling fluorometer collected the first over‐winter daily phytoplankton profiles Phytoplankton communities were differentially impacted by physical and chemical factors over long‐term versus seasonal time scales Phyoplankton groups are differentially competitive due to periods of higher nutrients versus light/energy limitation